Transitions from career employment among public- and private-sector workers. (11th February 2019) - Quinn, Joseph F.; Cahill, Kevin E.; Giandrea, Michael D.
Abstract: Do the retirement patterns of public-sector workers differ from those in the private sector? The latter typically face a retirement landscape with exposure to market uncertainties through defined-contribution pension plans and private saving. Public-sector workers, in contrast, are often covered by defined-benefit pension plans that encourage retirement at relatively young ages and offer financial security at older ages. We examine how private- and public-sector workers transition from full-time career employment, with a focus on the importance of gradual retirement. To our surprise, we find that the prevalence of continued work after career employment, predominantly on bridge jobs with new employers, is very similar in the two sectors, a result with important implications in a rapidly aging society.